(3OQGSGJ GdLOhi hJbjje GdeTQhYGJs - (3YHO GdbGOQ(B, (3HGHGs ((3YeGf(B:s (3ecJHI GdeLJeY GdYQHj ddfTQ hGdJhRjY,s, 2014)
(3jVe GdESJKeGQ aj GdacQ GdEbJUGOj heaGgje CSGSjI Mhd GdESJKeGQ hLOhi GdeTQhYGJ, OQGSGJ LOhi GdeTQhYGJ GdESJKeGQjI hGdJbjje GdeGdj ddeTQhYGJ, GdJbjje GdEbJUGOj ddeTQhYGJ(B( (3JMdjd GdQHMjI GdhWfjI(B)s
(3HHdjhZQGajG(B: (3U(B.333-338s
Keywords: (3GdeTQhYGJs; (3Jbjje GdCOGAs; (3OQGSI GdLOhis